How to build a story - Dowell, Frances O'Roark (Atheneum Books for Young Readers, 2020)
Provides students with a narrative guide to writing a story from beginning to end. Discusses story ideas, characters, plot, drafts, revisions, and editors. Also includes writing exercises in each chapter, and black-and-white illustrations.